2014
DOI: 10.1021/jm5012337
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Evaluation of Water-Soluble Iminophosphorane Ruthenium(II) Compounds. A Potential Chemotherapeutic Agent for Triple Negative Breast Cancer

Abstract: A series of organometallic ruthenium(II) complexes containing iminophosphorane ligands have been synthesized and characterized. Cationic compounds with chloride as counterion are soluble in water (70–100 mg/mL). Most compounds (especially highly water-soluble 2) are more cytotoxic to a number of human cancer cell lines than cisplatin. Initial mechanistic studies indicate that the cell death type for these compounds is mainly through canonical or caspase-dependent apoptosis, nondependent on p53, and that the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
121
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(142 citation statements)
references
References 76 publications
18
121
1
Order By: Relevance
“…While a linear Stern-Volmer plot is indicative of a single quenching mechanism, either dynamic or static, the positive deviation observed in the plots of F 0 /F versus [Q] of 1a or 1b (Figure 7(B)) suggests the presence of different binding sites in the protein. [81] A similar behavior was observed for iminophosphorane complexes of Ru(II), [6] Pd(II) or Pt(II) [82] reported by some of us. In the case of [MCl 2 (TPA=N-C(O)-2-NC 5 H 4 )] (M = Pd, Pt), isothermal titration calorimetry (ITC) [82] showed two different binding interactions which explained the lack of linearity observed in the fluorescence quenching studies, as the Stern-Volmer method assumes all binding sites to be equivalent.…”
Section: Resultssupporting
confidence: 78%
“…While a linear Stern-Volmer plot is indicative of a single quenching mechanism, either dynamic or static, the positive deviation observed in the plots of F 0 /F versus [Q] of 1a or 1b (Figure 7(B)) suggests the presence of different binding sites in the protein. [81] A similar behavior was observed for iminophosphorane complexes of Ru(II), [6] Pd(II) or Pt(II) [82] reported by some of us. In the case of [MCl 2 (TPA=N-C(O)-2-NC 5 H 4 )] (M = Pd, Pt), isothermal titration calorimetry (ITC) [82] showed two different binding interactions which explained the lack of linearity observed in the fluorescence quenching studies, as the Stern-Volmer method assumes all binding sites to be equivalent.…”
Section: Resultssupporting
confidence: 78%
“…2) which displayed similar IC 50 values in vitro for human cancer cell versus HEK-293T but which was very effective in vivo on MDA-MB-231 xenografts in NOD.CB17-Prkdc SCID/J mice while having low systemic toxicity. 33 The cytotoxicity of the most active dendrimers is in the range of the cytotoxicity obtained for two arene-ruthenium octanuclear dendrimers on cervical cancer cell lines (A2780 and A2780cisR). 49 In the case of these previously reported compounds (containing chelating N,O - and N,N -ruthenium (II) arene functionalized poly(propyleneimine) dendrimer scaffolds a correlation between size dependency of the dendrimers and cytotoxicity was found.…”
Section: Resultsmentioning
confidence: 95%
“…Most of the complexes were found to be more cytotoxic than cisplatin in several human cancer cell lines. 158 The most effective complex, 6k , produced a 56% decrease in tumor size in mice with xenografted breast carcinoma MDA-MB-231 cells, with low systemic toxicity after 28 days of treatment (14 doses of 5 mg/kg, every other day). Pharmacokinetic studies indicated that 6k appeared rapidly in plasma, with high uptake in the breast tumor tissues compared to the kidneys and liver.…”
Section: Arene Ruthenium(ii) Complexesmentioning
confidence: 99%